Structural and optical properties of Eu-doped at the site of Sr and Sn in Sr2SnO4 layered perovskite - Kumar U.; Yadav D.; Upadhyay G.N.S. (My University, 2025)
The structural and emission analysis of Sr2SnO4, Sr1.99Eu0.01SnO4, and Sr2Sn0.99Eu0.01O4 were analysed in detail. The thermal analysis of the mixture of raw materials reveals the reaction among the raw materials takes place around 1000°C. The Reitveld refinement of the x-ray diffraction data shows the solubility of Eu on both site of Sr2SnO4. Higher crystallite size and lattice strain were observed for Sr1.99Eu0.01SnO4 than Sr2Sn0.99Eu0.01O4, because Eu3+ acts as donor at Sr2+ site while as acceptor at Sn4+ site. Absences of any band associated with raw materials in Raman spectrum also confirm the monophasic nature of the sample. The photoluminescence (PL) spectra of Eu-doped samples exhibits strong peak at 612nm ascribed to electric dipole transition 5D0→7F2 of Eu3+ shows higher peak intensity and width for Sr1.99Eu0.01SnO4 than Sr2Sn0.99Eu0.01O4. © 2019 Author(s).